Fermentative biohydrogen production Evaluation of net energy gain - Perera, K.R.J.; Ketheesan, B.; Gadhamshetty, V.; Nirmalakhandan, N. (Elsevier, 2010)
Most dark fermentation (DF) studies had resorted to above-ambient temperatures to maximize hydrogen yield, without due consideration of the net energy gain. In this study, literature data on fermentative hydrogen production from glucose, sucrose, and organic wastes were compiled to evaluate the benefit of higher fermentation temperatures in terms of net energy gain. This evaluation showed that the improvement in hydrogen yield at higher temperatures is not justified as the net energy gain not only declined with increase of temperature, but also was mostly negative when the fermentation temperature exceeded 25 C. To maximize the net energy gain of DF, the following two options for recovering additional energy from the end products and to determine the optimal fermentation temperature were evaluated: methane production via anaerobic digestion (AD); and direct electricity production via microbial fuel cells (MFC). Based on net energy gain, it is concluded that DF has to be operated at near-ambient temperatures for the net energy gain to be positive; and DF þ MFC can result in higher net energy gain at any temperature than DF or DF þ AD.
Keywords: Biohydrogen; Dark fermentation; Net energy gain; Anaerobic digestion